Person-centered therapy and older adults’ self-esteem: A pilot study with followup - von Humboldt, Sofia (2013)
Objectives: A higher self-esteem (SE) is suggested by a reduced difference between ideal and real self. The present pilot study was designed to investigate if a brief eight-session individual person-centered therapy (PCT) intervention on older adults can promote their SE, as compared with a control group (waiting list). We hypothesized that participants randomized to PCT would report improvements in SE from pre- to post-intervention compared to those not attending PCT sessions. Method: We recruited 81 persons aged between 65- 82 years (M = 71.9, SD = 4.77) in the Great Lisbon area, in Portugal and randomized 40 to PCT and 41 to control group. The PCT intervention consisted of an eight weekly individual therapy. Measures were completed, including demographics and the Self-esteem Scale (SES) at the baseline, post-treatment and at the 12-month follow-up. Results: Findings indicated that individual PCT with older adults may improve their SE. The difference between ideal self and real self, evidenced at follow-up (M = 1.251, SD = .524) by the participants who had undergone PCT, was significantly lower (41.3%) in comparison to the baseline score (M = 2.131, SD = .799). Additionally, significant differences between the intervention group and the control group were found in the post-intervention and follow-up. Estimates were statistically significant at .05 level. Conclusions: Results suggest that PCT is beneficial for improving SE. Clinical practice and program development in therapeutic settings may benefit from including PCT as an important component for promoting SE in older adults and for aging well.